(untitled) (Journal of Naval Architecture and Marine Engineering, 2022)
The current study aims to explore stagnation spot flow of a micropolar liquid about a plain linear exponentially expanding penetrable surface in the incidence of chemical reaction and in-house heat production/absorption. Through similarity mapping, the mathematical modeling statements are reformed as ODE’s and numerical results are found by shooting techniques. The impact of varying physical constants on momentum, micro-rotation, temperature and concentration are demonstrated through graphs. The computed measures including shear, couple stress and mass transfer with distinct measures of factors involved in this proposed problem are presented through a table. The presence of heat source increases the temperature of the fluid but has no impact on the velocity, angular velocity and concentration.